Evaluation of Violence and its Management Experienced by Emergency Medical Service Workers in Lithuania’s Biggest Cities (Laisvalaikio tyrimai, 2020)
The purpose was to investigate violence experienced in work environment by emergency medical service workers of Lithuania’s biggest cities and methods of violence management.Methods – Questionnaire survey.Relevance of the research.  Violence and aggression in the workplace affect many fields and workers of different levels. However, healthcare sector has the highest risk of experiencing violence. In recent years, it was found that healthcare specialists were under substantial risk of experiencing violence from patients or their companions and it raises concern about the medical personnel. Although workers may experience violence and aggression in every healthcare field, it is more likely for the specialists providing emergency medical aid. Therefore, it is of great importance to put efforts into protecting emergency care providers and patients from incidents of aggression or violence in order to deliver quality care for the patients. The objective of this study was to explore violence in the workplace experienced by Lithuania’s biggest cities emergency medical service workers and ways it can be managed.Research results and conclusions. After the analysis of the survey results it was found that emergency medical service workers of Lithuania’s biggest cities most frequently experience violence in form of verbal aggression (on average 57 times a year), provocative aggressive behaviours (22 times a year) and threats (20 times a year). The rarest form of violence experienced was sexual harassment.After analysing the responses, it was noted that emergency medical service providers of Lithuania’s biggest cities experienced violence from patients in more than half of all cases and in about one third of cases of violence it was received from relatives. It should also be noted that a small part (one-tenth of all cases) of violence was received from colleagues at work.In situations of violence, emergency medical service workers try to hide their fear and do not retreat, they remain close to the exit door and try to reduce excessive triggers and noises that could escalate frustration.Keywords: violence, ambulance, aggression.